2021
DOI: 10.1038/s41598-020-80054-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid processing of fearful faces relies on the right amygdala: evidence from individuals undergoing unilateral temporal lobectomy

Abstract: Facial expressions of emotions have been shown to modulate early ERP components, in particular the N170. The underlying anatomical structure producing these early effects are unclear. In this study, we examined the N170 enhancement for fearful expressions in healthy controls as well as epileptic patients after unilateral left or right amygdala resection. We observed a greater N170 for fearful faces in healthy participants as well as in individuals with left amygdala resections. By contrast, the effect was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Therefore, at least the right amygdala's influence on visual emotion processing seems confined to specific timewindows in the processing stream. This had already been suggested by two previous smaller EEG studies on emotional face processing in amygdala-damaged individuals (Framorando et al, 2021;Rotshtein et al, 2010). The results by Mielke et al (2022) demonstrate that right medial temporal lobe structures are particularly involved in early visual emotion processing from complex scenes, while effects of right TLR can be compensated in later stages of cerebral processing, probably via recruitment of additional cortical structures and perhaps also due to the influence of the intact contra-resectional amygdala.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, at least the right amygdala's influence on visual emotion processing seems confined to specific timewindows in the processing stream. This had already been suggested by two previous smaller EEG studies on emotional face processing in amygdala-damaged individuals (Framorando et al, 2021;Rotshtein et al, 2010). The results by Mielke et al (2022) demonstrate that right medial temporal lobe structures are particularly involved in early visual emotion processing from complex scenes, while effects of right TLR can be compensated in later stages of cerebral processing, probably via recruitment of additional cortical structures and perhaps also due to the influence of the intact contra-resectional amygdala.…”
Section: Discussionsupporting
confidence: 64%
“…Rotshtein et al (2010) report reduced P1 and late positive potentials, but intact N1 and mid‐latency responses, in seven patients with sclerosis in either the left or the right amygdala. Framorando et al (2021) identified an N1 impairment in six right amygdalo‐hippocampectomy patients, but not in eight additional left amygdalo‐hippocampectomy patients. Theoretical considerations raise the possibility of distinct mTL contributions to emotion processing in specific time windows, which is supported by preliminary data, but any impact may depend on the stimuli employed, precluding generalization from emotional faces or body language to complex scenes.…”
Section: Introductionmentioning
confidence: 99%
“…However, highly time‐resolved electrophysiology measures may yield results that are different from or complementary to hemodynamic studies. So far, to our knowledge, only two electrophysiology studies investigated to what extent the mTL contributes to the generation of emotion‐sensitive surface ERPs (Framorando, Moses, Legrand, Seeck, & Pegna, 2021; Rotshtein et al, 2010). Both studies focused on face processing and found dampened responses to fearful faces on different ERPs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the amygdala to respond before visual cortex to subliminal emotional faces (Bayle et al, 2009). In relation to this, the amygdala’s role as an early detector or evaluator of emotional stimuli -not only subliminal-capable of modulating the subsequent activity of the visual cortex has been often postulated (e.g., Framorando et al, 2021; Krolak-Salmon et al, 2004; Sabatinelli et al, 2009; Vuilleumier, 2005). Whether this previous evaluation of the amygdala is preceptive for the visual cortex activity to be modulated by emotional stimulation is, however, unclear.…”
Section: Introductionmentioning
confidence: 99%